KONSEP ADAB GURU DAN MURID MENURUT AL-GHAZALI DAN RELAVANSINYA DI ERA MODERN - Naila Faza Aisyi Nadlira; Nabila Mufidah Aulia; Nadiyah Qurrata A’yun; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This study examines the principles of etiquette between teachers and students as articulated by Imam Al-Ghazali and their relevance in contemporary educational contexts. Islamic education emphasizes not only the development of intellectual abilities but also the cultivation of moral character and ethics. Using a literature review and content analysis approach, this study explores literature on teacher-student etiquette, Islamic educational ethics, and the challenges emerging in the era of digital learning. The findings indicate that maintaining proper etiquette between teachers and students plays a critical role in educational success, fostering harmonious interactions, and ensuring that acquired knowledge brings blessings. In the digital era, the use of social media and online learning can alter interaction patterns, diminish respect for teachers, and create an imbalance between academic achievement and moral development. Therefore, integrating the values of etiquette, strengthening character education, and positioning teachers as moral exemplars are key strategies in modern education.